Robotization of agriculture in the world - Sydorenko, D. O. (ТДАТУ, 2020)
The article deals with the problem of automation and robotization of agricultural operations. The spheres of application were considered as well as prospects and difficulties. Some statistic data was also nalized.
Keywords: automation; robotization; innovative developments